Human Capital Affects Religious Identity: Causal Evidence from Kenya - Livia Alfonsi; Michal Bauer; Julie Chytilová; Edward Miguel (Institute of Labor Economics (IZA), 2023)
We study how human capital and economic conditions causally affect the choice of religious denomination. We utilize a longitudinal dataset monitoring the religious history of more than 5,000 Kenyans over twenty years, in tandem with a randomized experiment (deworming) that has exogenously boosted education and living standards. The main finding is that the program reduces the likelihood of membership in a Pentecostal denomination up to 20 years later when respondents are in their mid-thirties, while there is a comparable increase in membership in traditional Christian denominations. The effect is concentrated and statistically significant among a sub-group of participants who benefited most from the program in terms of increased education and income. The effects are unlikely due to increased secularization, because the program does not reduce measures of religiosity. The results help explain why the global growth of the Pentecostal movement, sometimes described a "New Reformation", is centered in low-income communities.
Keywords: C93; O12; Z12; 330; religion; identity; human capital; Kenya